ON THE POSSIBILITY OF GROUP-THEORETIC DESCRIPTION OF AN EQUIVALENCE RELATION CONNECTED TO THE PROBLEM OF COVERING SUBSETS IN FINITE FIELDS WITH COSETS OF LINEAR SUBSPACES - Sargsyan, D.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
Let $ F^{n}_{q} $ be an $ n $-dimensional vector space over a finite field $ F_q $ . Let $ C(F^{n}_{q} ) $ denote the set of all cosets of linear subspaces in $ F^{n}_{q} $. Cosets $ H_1, H_2, … H_s $ are called exclusive if $ H_i subseteq H_j $, $ 1 \mathclose{≤} i \mathclose{
Keywords: finite field; coset; covering; bijection; linearized disjunctive normal form; general affine group; general semiaffine group